2020
DOI: 10.1093/mnras/staa1042
|View full text |Cite
|
Sign up to set email alerts
|

EX draconis: using eclipses to separate outside-in and inside-out outbursts

Abstract: We present a study of the eclipses in the accreting white dwarf EX draconis (EX Dra) during TESS Cycles 14 and 15. During both of the two outbursts present in this data set, the eclipses undergo a hysteretic loop in eclipse-depth/out-of-eclipse-flux space. In each case, the direction in which the loops are executed strongly suggests an outburst that is triggered near the inner edge of the accretion disc and propagates outwards. This in turn suggests that the outbursts in EX Dra are ‘inside out’ outbursts; even… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…With a steady supply of mass, the inner part of the accretion disk of IW And-type stars can stay in a hot state in both quasi-standstill and brightening phases. Once the mass threshold has been achieved in the outer disk, brightening could occur from inside to outside of the disk, known as insideout brightening (Court et al 2020;Kimura et al 2020a). The brightening event, in fact, shows up in the light curve (for example, see Figure 3 at JD 2,458,565).…”
Section: Photometric Characteristicsmentioning
confidence: 99%
“…With a steady supply of mass, the inner part of the accretion disk of IW And-type stars can stay in a hot state in both quasi-standstill and brightening phases. Once the mass threshold has been achieved in the outer disk, brightening could occur from inside to outside of the disk, known as insideout brightening (Court et al 2020;Kimura et al 2020a). The brightening event, in fact, shows up in the light curve (for example, see Figure 3 at JD 2,458,565).…”
Section: Photometric Characteristicsmentioning
confidence: 99%
“…NSHs have been observed during both DN outbursts and quiescence (e.g., V503 Cyg, Harvey et al 1995;ER UMa, Ohshima et al 2012;BK Lyn, Kato et al 2013;V1504 Cyg, Ohshima et al 2014V344 Lyr, Wood et al 2011;SDSS J210014.12+004446.0, Olech et al 2009;NY Her, Pavlenko et al 2021). However, Ramsay et al (2017) and Court et al (2020) studied Z Cam-type DNe V729 Sgr and EX Dra and both found NSHs only in quiescence and not during outbursts, demonstrating that there is no consensus on the existence of NSHs during DN outbursts. Our recent work found that the NSHs in the Z Cam-type DN AH Her change as the outburst progresses (Sun et al 2023a).…”
Section: Introductionmentioning
confidence: 99%